Control of RNA degradation in cell fate decision - Deng, Mingqiang; Wang, Xiwei; Xiong, Zhi; Tang, Peng (Frontiers in Cell and Developmental Biology, 2023)
Cell fate is shaped by unique gene expression program, which reflects the concerted action of multilayered precise regulation. Substantial research attention has been paid to the contribution of RNA biogenesis to cell fate decisions. However, increasing evidence shows that RNA degradation, well known for its function in RNA processing and the surveillance of aberrant transcripts, is also broadly engaged in cell fate decisions such as the maternal-to-zygotic transition, stem cell differentiation or somatic cell reprogramming etc. In this review, we firstly take a glimpse at diverse RNA degradation pathways in the cytoplasm and in the nucleus, then we summarize how selective transcript clearance is regulated and integrated into the gene expression regulation network for the establishment, maintenance and exit from special cellular state.